Flow Experiences in Mobile Assisted Language Learning Among EFL Tertiary Students in Henan, China - Qiong, Xiao (UNIVERSITI MALAYSIA SARAWAK, 2025)
Despite the widely recognised benefits of mobile-assisted language learning (MALL), concerns persist regarding its effectiveness and the issue of low learner engagement. These challenges necessitate further investigation, particularly from a psychological perspective. Within educational settings, flow, the mental state of operation in which a person performing an activity is fully immersed in a feeling of energized focus, full involvement, and enjoyment in the process of the activity, provides a valuable framework for fostering student engagement and optimising learning experiences, which are essential for effective language acquisition. However, existing MALL research has predominantly employed cognitive approaches, with limited attention given to students’ psychological and affective states. To address this gap, this study integrates flow theory and PAT model into MALL context to examine the overall flow experiences, its influencing factors and its impact on perceived learning among Chinese tertiary students during English learning on a mobile platform Rain Classroom. An explanatory sequential mixed method was employed to collect quantitative and qualitative data via questionnaire-based survey and semi-structured interview. The research retrieved 450 questionnaires from an online questionnaire platform from an online questionnaire platform, and 16 students participated the semi-structured interview. Purposive sampling was employed at both the quantitative and qualitative stages. Descriptive analysis, difference analysis, correlational analysis and SEM analysis were conducted to analyse quantitative data. Thematic analysis was conducted to analyse qualitative data. The findings revealed that Chinese college students experienced moderate level of flow in English study on the mobile learning platform, experiencing enjoyment most and focused attention the least. Moreover, significant difference was revealed in perception of task challenges among students in high-performing group and low-performing group. However,no significant differences in terms of English proficiency level were identified in other constructs. Furthermore, person factors, artefact factors and task factors were all found to be significantly related to overall flow experiences, with artefact factors having strongest impact on flow, followed by the person related factors. However, task challenge factors were found to have negative impact on flow experience. In addition, flow experience was found to be strongly related to the perceived learning, evidenced by improved English skills and enhanced engagement and participation among participants. The Structural Equation Modelling analysis confirmed the four hypotheses and the explanatory power of the conceptual mode was strong and sound. The explained variance R 2 for flow and perceived learning were 0.571 and 0.403, which meant that 57.1% of variance of the flow experience of college students in China during in mobile English learning could be explained by the person factors, artefact factors and task factors together and 40.3% of the perceived learning could be explained by the flow experience. Therefore, the Flow in Mall model developed for the EFL program was confirmed to be suitable and robust with good explanatory power. Moreover, motivation, self-discipline, personal mental and physical states, teacher’s charisma, engaging contents, distractions were identified in thematic analysis as additional factors that could influence flow experience in mobile mediated language learning. This study provides insights for both practitioners and educators in finding an effective way to improve both the students’ psychological positive experience and their overall learning experience and thus promote learning flow and engagement throughout the mobile language learning process.